Exercise improves intestinal IgA production by T-dependent cell pathway in adults but not in aged mice - Hernández-Urbán, Angel Joel; Drago-Serrano, Maria Elisa; Cruz-Baquero, Andrea; García-Hernández, Ana Lilia; Arciniega-Martínez, Ivonne Maciel; Pacheco-Yépez, Judith; Guzmán-Mejía, Fabiola; Godínez-Victoria, Marycarmen (Frontiers in Endocrinology, 2023)
Introduction. Hypermutated high-affinity immunoglobulin A (IgA), neutralizes toxins and drive diversification of bacteria communities to maintain intestinal homeostasis although the mechanism underlies the impact of moderate aerobic exercise (MAE) on the IgA-generation via T-dependent (TD) is not fully know. Therefore, the aim of this study was to determine the effect of long-time MAE on production of IgA through TD pathway in Peyer´s patches of the small intestine from aged mice. Methods. MAE protocol consisted of twenty 3-months old (young) BALB/c mice running in an endless band at 0º inclination and a speed of 10 m/h for 5 days a week and resting 2 days on the weekend until reaching 6-month-old (adulthood, n=10) or 24-month-old (aging, n=10). Groups of young, adult or elderly mice were included as sedentary controls (n=10/per group). At 6 or 24 months old, all were sacrificed, small intestine samples were dissected to prepare intestinal lavages for IgA quantitation by ELISA and to obtain suspensions from Peyer´s patches (PP) and lamina propria (LP) cells for analysis of T, B and plasma cell subpopulations by flow cytometry and mRNA analysis expression by RTqPCR of molecular factors related to differentiation of B cells to IgA+ plasma cells, class switch recombination and IgA-synthesis. Statistical analysis was computed with two-way ANOVA (factor A=age, factor B=group) and p<0.05 was considered for statistically significant differences. Results. Compared to age-matched sedentary control, in exercised elderly mice parameters were either increased (IgA concentration, IL-21, IL-10 and RDH mRNA expression), decreased (α-chain mRNA, B cells, mIgA+ B cells, mIgM+ B cells and IL-4 mRNA) or unchanged (PP mIgA+ plasmablasts and LP cyt-IgA+ plasma cells). Regarding the exercised adult mice, they showed an upmodulation of IgA-concentration, mRNA expression IL-21, IL-10 and RDH and cells (PP B and T cells, mIgM+ plasmablasts and LP cyt-IgA+plasma cells). Conclusion. Our findings suggest that MAE restored the IgA production in adult mice via TD cell pathway but does not in aged mice. Other studies are necessary to know in more detail the impact of long-time MAE on TD pathway to produce IgA in aging.